The Relationship between Exchange Rate Volatility and Foreign Direct Investment in Turkey: Toda and Yamamoto Causality Analysis - KILIÇARSLAN, Zerrin (International Journal of Economics and Financial Issues, 2018)
Many countries have embraced the floating exchange rate system with the collapse of the Bretton Woods system. As a result of the transition to the floating exchange rate system, the volatilities in exchange rates have become a major problem for countries. The volatility in exchange rates affects the expected benefits of foreign direct investments as it increases uncertainty for investors. Therefore, foreign direct investment has become one of the important factors affecting the flow of investment. In this study, the relationship between exchange rate volatility and foreign direct investment in Turkey for the period 2005Q4-2018Q1 was analyzed using Toda-Yamamoto causality test. Real effective exchange rate volatility is estimated using the GARCH model. As a result, a one-way causality relationship from foreign direct investments to exchange rate volatility has been found. Keywords: Foreign direct investment, exchange rate volatility, Toda and Yamamoto Causality JEL Classifications: F21, F31, C22